2014
DOI: 10.1016/j.redox.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetically induced oxidative stress in mice causes thrombocytosis, splenomegaly and placental angiodysplasia that leads to recurrent abortion

Abstract: Historical data in the 1950s suggests that 7%, 11%, 33%, and 87% of couples were infertile by ages 30, 35, 40 and 45, respectively. Up to 22.3% of infertile couples have unexplained infertility. Oxidative stress is associated with male and female infertility. However, there is insufficient evidence relating to the influence of oxidative stress on the maintenance of a viable pregnancy, including pregnancy complications and fetal development. Recently, we have established Tet-mev-1 conditional transgenic mice, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…81 Additionally, Tet-mev-1 conditional transgenic mice, which have a dysfunctional mitochondrial respiratory chain, can mimic OS-related miscarriage. 82 Thus, both CBA/J 9 DBA/2 and Tet-mev-1 mice can link placental OS with pregnancy losses and provide powerful animal models for the evaluation of better treatment approaches. 81,82 Immune microenvironment and spontaneous abortion uNK cells may be biologically necessary to maintain successful pregnancy.…”
Section: Role Of Os In Spontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Additionally, Tet-mev-1 conditional transgenic mice, which have a dysfunctional mitochondrial respiratory chain, can mimic OS-related miscarriage. 82 Thus, both CBA/J 9 DBA/2 and Tet-mev-1 mice can link placental OS with pregnancy losses and provide powerful animal models for the evaluation of better treatment approaches. 81,82 Immune microenvironment and spontaneous abortion uNK cells may be biologically necessary to maintain successful pregnancy.…”
Section: Role Of Os In Spontaneous Abortionmentioning
confidence: 99%
“…82 Thus, both CBA/J 9 DBA/2 and Tet-mev-1 mice can link placental OS with pregnancy losses and provide powerful animal models for the evaluation of better treatment approaches. 81,82 Immune microenvironment and spontaneous abortion uNK cells may be biologically necessary to maintain successful pregnancy. [83][84][85] However, Clifford et al 86 showed increased CD56 + NK cells in the endometrium of recurrent early abortion, which suggests a possible role for NK cells in this disease.…”
Section: Role Of Os In Spontaneous Abortionmentioning
confidence: 99%
“…This further lead to the inflammation of the placenta and abnormal angiogenesis and resulted in spontaneous abortion. Thus oxidative stress influences the occurrence of RPL [22].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Tet‐mev‐1 conditional transgenic mice grew to normal size in 12 weeks after suffering of low birthweight and initial growth retardation. They had low fertility and recurrent miscarriages (Ishii et al ., , ). After normal development, male and female Tet‐mev‐1 mice showed accelerated corneal dysfunctions with age, that is , delayed epithelialization with keratitis, decreasing endothelial cells such as Fuch's corneal dystrophy, and thickened Descemet's membrane (Onouchi et al ., ).…”
Section: Introductionmentioning
confidence: 99%